The Argentine competition law and its enforcement - Germán Coloma (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2007)
This article analyzes the basic characteristics of the Argentine competition law and the way in which it has been enforced in several important antitrust cases. We begin with a section that introduces the evolution of the law, followed by another section about the basic economic and legal principles underlying that law. The rest of the article describes the enforcement of the law, in a number of cases that involve collusive practices, exclusionary practices, vertical restraints, abuses of dominant position, and mergers.
Keywords: K21; L40; 330; competition law; antitrust; Argentina; Wettbewerbsrecht; Kartellrecht; Argentinien